Protective effect of aqueous extract from spirulina platensis against cell death induced by free radicals - Chu, Wan Loy; Lim, Yen Wei; Radhakrishnan, A.K.; Lim, Phaik Eem (BioMed Central, 2010)
Background: Spirulina is a commercial alga well known to contain various antioxidants, especially phycocyanin. Apart from being sold as a nutraceutical, Spirulina is incorporated as a functional ingredient in food products and beverages. Most of the previous reports on antioxidant activity of Spirulina were based on chemical rather than cell-based assays. The primary objective of this study was to assess the antioxidant activity of aqueous extract from Spirulina based on its protective effect against cell death induced by free radicals. Methods: The antioxidant activity of the cold water extract from food-grade Spirulina platensis was assessed using both chemical and cell-based assays. In the cell-based assay, mouse fibroblast cells (3T3) cells were incubated for 1 h in medium containing aqueous extract of Spirulina or vitamin C (positive control) at 25, 125 and 250 mu g/mL before the addition of 50 mu M 1,1-diphenyl-2-picrylhydrazyl (DPPH) or 3-ethylbenzothiazoline-6-sulfonic acid (ABTS). The cells were incubated for another 24 h before being assessed for cell death due to apoptosis using the Cell Death Detection ELISA Kit. Spectrophotometric assays based on DPPH and ABTS were also used to assess the antioxidant activity of the extract compared to vitamin C and vitamin E (positive controls). Results: Spirulina extract did not cause cytotoxic effect on 3T3 cells within the range of concentrations tested (0 250 mu g/mL). The extract reduced significantly (p < 0.05) apoptotic cell death due to DPPH and ABTS by 4 to 5-fold although the activity was less than vitamin C. Based on the DPPH assay, the radical scavenging activity of the extract was higher than phycocyanin and was at least 50% of vitamin C and vitamin E. Based on the ABTS assay, the antioxidant activity of the extract at 50 mu mug/mL was as good as vitamin C and vitamin E. Conclusions: The results showed that aqueous extract of Spirulina has a protective effect against apoptotic cell death due to free radicals. The potential application of incorporating Spirulina into food products and beverages to enhance their antioxidant capacity is worth exploring.